Empowerment of the Elderly With Joint Pain Through Exercise Relaxation Progressive Muscles in UPT PSTW Jember - Elsa Yolanda Talapessy; Nova Febriani Nurhaliza; Erwindyah Nur Widiyanti; Emilia Fitri Wulandari; Annisa Fitriana; Tantut Susanto (Journal of Health Community Service, 2025)
Background: The elderly are a vulnerable age who experience various problems, especially the problem of physical dissatisfaction which results in disturbances in musculoskeletal function. Disorders that often arise are joint pain that makes the elderly experience disruption of daily activities. Osteoarthritis (OA) is a degenerative disease that causes chronic inflammation due to friction between the ends of the bones that make up the joints. Therapy that can be used to reduce joint pain is progressive muscle relaxation therapy. Progressive muscle relaxation is a relaxation technique that combines deep breathing exercises and several contraction and relaxation techniques of certain muscles. Study aims to determine the effect of progressive muscle relaxation therapy on reducing joint pain in the elderly at Wisma Dahlia UPT PSTW Jember. Method: Experimental study with a quasi-experimental research design with a pretest and posttest one group design approach where in this study compares the pretest and posttest values of the elderly pain scale after giving progressive muscle relaxation therapy at Wisma Dahlia UPT PSTW Jember. Results and Discussion: Almost all the elderly at Wisma Dahlia have complaints, namely joint pain with a percentage of 86.4% with a pain scale of 4-6 before being given therapy. After 3 sessions of progressive muscle relaxation exercise there was a decrease in the level of pain before and after progressive muscle relaxation exercise from moderate pain (4-6) from 61.5% to 15.3% pain. In addition, there was an increase in the number of mild pain (1-3) from 38.5% to 84.7%. The p-value is 0.018 <0.05, which means that there are differences in the level of pain in the elderly before and after the progressive muscle relaxation intervention. The decrease in pain scale in the elderly shows that progressive muscle relaxation therapy is able to effectively reduce pain by increasing endorphins in the body to inhibit the transmission of painful stimuli. Conclusion: The elderly at Wisma Dahlia UPT PSTW Jember after participating in the empowerment of progressive muscle relaxation exercises for 1 week, their joint pain complaints decreased. Progressive muscle relaxation needs to be included in the PSTW exercise program that can be done routinely so that it can reduce joint pain experienced by the elderly.